Dysgerminoma with Estrogen-Producing Functioning Stroma Presenting Precocious Puberty - Shunsuke Nagase; Kanako Ogura; Karin Ashizawa; Nana Nakazawa-Tanaka; Masahiko Urao; Masaharu Fukunaga; Yuto Yamazaki; Hironobu Sasano; Toshiharu Matsumoto (Hindawi Limited, 2021)
Dysgerminoma is a malignant ovarian germ cell tumor, and unlike sex-cord stromal tumors, endocrine manifestation is considered rare. Here, we report the first case of dysgerminoma presenting precocious puberty. The patient is a 7-year-old girl who presented with a breast development in Tanner stage 3. Serum estradiol (E2) was markedly elevated while luteinizing hormone (LH) and follicle-stimulating hormone (FSH) were suppressed below the detection limit. Microscopically, the right ovarian mass displayed nests of large polygonal cells and fibrous septa which were focally concentrated by theca-like plump spindle cells. Immunohistochemistry revealed that the spindle cells expressed various steroidogenic enzymes involved in estrogen biosynthesis including P450 aromatase. The tumor was diagnosed with pure dysgerminoma with estrogen-producing functioning stroma. After the operation, serum E2 declined below the detection limit; LH and FSH returned within the normal range. This case demonstrates that even a conventional dysgerminoma can present endocrine manifestation through functioning stroma.